Gendered seed production and delivery models across 10 countries in Sub-Saharan Africa - Manoti, Dismas; Gwaka, Josky; Nchanji, Eileen; Lutomia, Cosmas; Yila, Jummai; Puskur, Ranjitha (2024)
The study was conducted in 10 African countries where 166 bean seed production and delivery actors were interviewed. The survey intended to document various production and delivery models used across the regions, the extent to which they involve and benefit women and vulnerable groups, the extent to which they promote availability and access to high-quality seeds, and examine the measures put in place to ensure high-quality seeds reach last mile farmers. The study participants were nongovernmental organizations (NGOs), national agricultural research system (NARS), seed companies and farmer seed producer groups. Purposive sampling was used due to the limited number of bean seed actors along the chain ready to provide information on their activities. Data was collected using the surveyCTO platform and it was managed and analyzed using the Statistical Package for Social Sciences software (SPSS), version 20.